Homocysteine level at the acute stage of ischemic stroke as a biomarker of poststroke depression: A systematic review and meta-analysis - Liang, Yanling; Shi, Xiangqun; Chen, Lue; Li, Yongxin; Zhong, Jianping (Frontiers in Psychiatry, 2023)
Background: Studies on the association of homocysteine level with poststroke depression (PSD) have yielded conflicting results. This systematic review and meta-analysis aimed to evaluate the elevated homocysteine level at the acute stage of ischemic stroke in predicting PSD. Methods: Two authors systematically searched articles indexed in PubMed and Embase database until to January 31, 2022. Studies evaluating the association of homocysteine level with the development of PSD in acute ischemic stroke patients were selected. Results: Ten studies involving 2907 patients were identified. The pooled adjusted odds ratio (OR) of PSD was 3.72 (95% confidence intervals [CI] 2.03–6.81) for the top versus bottom homocysteine level. The value of elevated homocysteine level in predicting PSD was stronger in ≥ 6-month follow-up (OR 4.81;95% CI 3.12–7.43) than those ≤ 3-month follow-up subgroup (OR 3.20;95% CI 1.29–7.91). Moreover, per unit increase in homocysteine level conferred a 7% higher risk of PSD. Conclusions: Elevated homocysteine level in the acute stage of ischemic stroke may be an independent predictor of PSD.